The metareticulate pollen morphology of Alternanthera Forssk. (Gomphrenoideae, Amaranthaceae) and its taxonomic implications. Issue 4 (1st October 2016) - Sánchez-del Pino, Ivonne; Fuentes-Soriano, Sara; Solis-Fernández, Karen Z.; Pool, Rolando; Alfaro, Rita
Abstract: Alternanthera (Amaranthaceae) is a diverse genus largely restricted to the American Tropics that belongs to the alternantheroid clade containing C4 and C3 –C4 intermediate species. This research focuses on the study of pollen characters by studying 13 species, representatives of the two major clades and subclades of Alternanthera . General palynological comparisons were conducted with light microscopy (LM), scanning electron microscopy (SEM) and with confocal laser scanning microscopy (CLSM) for exine ultrastructure. Twenty-five characters were measured and described for Alternanthera and among these, 14 pollen characters were used to discriminate pollen groups using cluster analysis and canonical analysis of principal coordinates (CAP). Pollen form and ornamentation, pores number, spines length, number of ektexinous bodies and nanospines on the ektexinous bodies on pore membranes, arrangement of nanopores and spines on structural elements, and metareticula form were taxonomically important and therefore used to construct the first palynological key to the alternantheroid clade species. Our study indicates that the seemingly subtle morphological variation of pollen is useful for recognising three main pollen types within Alternanthera . The much needed palynological terminology for describing the mesoporium in the metareticulate pollen of Amaranthaceae is provided.